Pregnant Women Infected with Coronavirus Disease 2019 Pneumonia: A Case Series in Medan, Indonesia - Sinaga, Bintang Yinke Magdalena; Ananda, Fannie Rizki (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Pregnancy state affects the immune regulation including physical barrier, innate, and adaptive immunity-related to susceptibility of infections and increasing risk for severe to critical case of COVID-19. Further, high risk of thrombosis becomes a challenge in the management of COVID19 in pregnancy due to the strong association with worse outcome. CASE REPORT: Here, we present three cases of pregnant women infected with COVID-19 pneumonia with different outcomes in maternal and fetal condition related to high-risk thrombosis. Serial inflammatory markers were needed to the early detect the disease progressivity in pregnant women with COVID-19. Further, complete assessment of fetus including reverse transcriptase-polymerase chain reaction and chest X-ray must be performed to the early diagnosis of COVID-19 in neonatal whose mother was infected by SARS-CoV-2. CONCLUSION: Pregnancy state affects the immune regulation including physical barrier, innate, and adaptive immunity-related to susceptibility of infections and increasing risk for severe to critical case of COVID-19. Further, high risk of thrombosis becomes a challenge in the management of COVID19 in pregnancy due to the strong association with worse outcome. Although fetal transmission of COVID-19 to fetus remains unclear, complete assessment of fetus including RT-PCR, and chest X-ray must be performed to the early diagnosis of COVID-19 in neonatal whose mother was infected by SARS-CoV-2.